Manure management practices and policies in sub-Saharan Africa: Implications on manure quality as a fertilizer - Ndambi, O.A.; Pelster, David E.; Owino, Joseph; Buisonjé, F. de; Vellinga, Theun V. (Frontiers Media, 2019)
Manure has been used as a fertilizer since ancient times and if well managed it can be an asset, promoting sustainable agriculture and increasing crop production, particularly for smallholder farmers in sub-Saharan Africa (SSA). However, most farmers in SSA do not apply recommended manure management practices, such as roofing animal housing, having a water-proof floor or covering manure during storage, causing large nutrient losses during manure storage, increasing greenhouse gas emissions and reducing the quality of the manure as a fertilizer. This paper compares manure management practices in representative SSA countries, and summarizes government policies and socio-cultural practices that influence the adoption of good (recommended) manure management practices. Three steps were applied in this analysis: i) review of manure management practices from various literature sources, ii) interviews on manure management practices and policies with key stakeholders from 13 SSA countries, and iii) surveys of manure management practices on small, medium and large scale farms in Ethiopia and Malawi. The review confirms the potential of manure to improve crop yields and promote sustainable agriculture in SSA. Unfortunately, most SSA countries a) do not explicitly mention manure management in their policies b) have different ministries that share responsibilities on manure management, often leading to incoherent policies and abnegation of these responsibilities c) take limited action to promote good practices or enforce legislation on manure management. Also, the field survey indicated that farmers lack knowledge on manure management. However, farmers are able to access agricultural extension services from both government and non-government agencies, although these extension services rarely included information on improved manure management practices. Extension services that encourage exchange and interaction between farmers were most successful in increasing adoption of good manure management practices, and are recommended. In addition, efforts to improve manure management in SSA should strengthen the enforcement of existing policies and provide an enabling environment for adoption of good manure management practices.